Effect of light intensity on indoor temperature and air velocity: A simulation study - Akop, Mohd Zaid; Shehab, Salem Saleh Omar; Masripan, Nor Azmmi; Abdul Hamid, Nurfaizey; Wasbari, Faizil; Md. Saad, Adzni; Mansor, Muhd Ridzuan; Noordin, Aminurrashid; Herawan, Safarudin Gazali (Universiti Malaysia Perlis, 2022)
It is essential to understand the factors influencing thermal responses to improve human comfort and properly reduce energy consumption. It has been confirmed that parameters unrelated to the thermal environment can influence the thermal responses of occupants. These factors are yet to be investigated and studied in detailed, especially under different environmental conditions because of insufficient knowledge about indoor environment factor interactions. Therefore, accurate and high-quality data of light intensity is highly important to be focused on. Accordingly, the influences of light intensity on the temperature and air velocity of the indoor environment were studied and investigated under natural and controlled environmental conditions. The main objectives are to investigate and evaluate various effects of light intensity parameters on the indoor room temperature and air velocity for the indoor environmental condition. An effect of light intensity and simulation analysis for the indoor environment was performed using the ANSYS platform. The main parameters such as indoor temperature and air velocity were measured. Based on the results obtained from simulation analysis, the halogen lamps possess an enormous influence on the indoor environmental parameters than the LED lamps; the light intensity is directly proportional to the air velocity and indoor temperature. Conclusively, the results of this study can be considered as a reinforcement step in emphasizing the actual effect of lighting intensity, and the required lighting must be in accordance with the daily duty.